MOTIVASI MEMODERASI PENGARUH KEPEMIMPINAN TERHADAP KEPUASAN KERJA PEGAWAI PT. NOK PRECISION COMPONENT BATAM - Yasripul; Hazriyanto; Yasripul Yasripul; Hazriyanto Hazriyanto (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the influence of leadership on job satisfaction by positioning motivation as a moderating variable at PT. Nok Precision Component Batam. Field phenomena indicate a need to understand whether employee motivation can strengthen leadership effectiveness in creating job satisfaction within the precision manufacturing industry. This research employs a causal associative quantitative approach, with data collection conducted via Likert-scale questionnaires. The population includes all permanent employees, with a sample of 54 respondents selected using simple random sampling techniques. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) via SmartPLS 3.0 software. The results of the first hypothesis test show that leadership has a positive and significant effect on job satisfaction, with a path coefficient of 0.740 and a P-Value of 0.000. However, the second hypothesis test results reveal that motivation does not significantly moderate the influence of leadership on job satisfaction (P-Value 0.408 > 0.05). These findings indicate that employee job satisfaction is more dominantly determined by leadership quality rather than internal motivation fluctuations. The practical implication for management is the necessity of strengthening managerial competence for leaders as the primary strategy to maintain employee job satisfaction stability